Implementation of Distribution Non-Cash Food Aid (BPNT) in Reducing The Expenditure Burden of Poor Families Based on an Islamic Perspective: Case Study of Aek Hamlet West Torop, Asam Jawa Village, District. Torgamba, District. South Labuhan Batu - Dini Rahmayani; Maidalena; Aqwa Naser Daulay (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Non-Cash Food Assistance (BPNT) is a central government program to help the poor who are food insecure. The purpose of this study is the implementation of non-cash food assistance expenditures in reducing the expenditure burden of poor families. This research uses a qualitative approach that produces descriptive data, by interviewing two poor people and one government. The data collection techniques applied are interviews, observation and documentation. The results of this study indicate that poverty reduction so far has only changed from the food subsidy system (Raskin / Rastra) with an in-kind scheme to the BPNT food assistance system with a non-cash scheme. each poor family receives assistance of Rp. 200,000, -. The implementation of the assistance program in reducing the expenditure burden of poor families reaches an effectiveness level of 66.57%, this shows